Rebalancing in the Euro Area and Cyclicality of Current Account Adjustments - Tressel, Thierry (IMF Working Papers; Working Paper ;, 2014)
The paper examines progress with the external rebalancing of euro area deficit countries. Relative prices are adjusting at different pace across countries and with different compositions of wage cuts and labor shedding. There is so far limited evidence of resource re-allocation from non-tradable to tradable sectors, while improved export performance is still dependent on external demand from the rest of world. Current account adjustments have taken place, reflecting structural changes but also cyclical forces, suggesting that part of the improvements may unwind when cyclical conditions improve. Looking ahead, relying only on relative price adjustments (which adversely affects demand) to rebalance the euro area could prove very challenging. Structural reforms will play an important role in the reallocation of resources to the tradable sector and the associated relative price adjustment, while boosting non-price and price competitiveness.